Trypanosoma equiperdum Low Molecular Weight Proteins As Candidates for Specific Serological Diagnosis of Dourine - Luciani, Mirella; Di Febo, Tiziana; Orsini, Massimiliano; Krasteva, Ivanka; Cattaneo, Angela; Podaliri Vulpiani, Michele; Di Pancrazio, Chiara; Bachi, Angela; Tittarelli, Manuela (Frontiers in Veterinary Science, 2018)
The diagnosis of dourine could be difficult because the clinical signs of this disease in horses are similar to those of surra, caused by Trypanosoma evansi. Moreover, T. equiperdum and T. evansi are closely related and, to date, cannot be distinguished using serological tests. A chemiluminescent immunoblotting assay (cIB) was developed to characterise the Trypanosoma equiperdum antigen pattern recognised by antibodies from naturally and experimentally dourine-infected horses and to analyse the kinetics of humoral response following the infection. In the first phase of the study, we tested a total of 20 sera from naturally and experimentally infected horses and from healthy control animals. cIB analysis revealed that antibodies from infected horses, in contrast to antibodies from uninfected horses, specifically recognise a T. equiperdum antigenic profile with low molecular weight bands ranging between 6 and 37 kDa. In the second part of the study, we tested other 615 sera (7 from naturally infected horses and 608 sera from healthy horses): results confirmed the data obtained previously. In addition, proteins in six bands with molecular weight ranging from 10 to 37 kDa were analysed by mass spectrometry, in order to identify immunogenic proteins that could be used as biomarkers in the diagnosis of dourine. A total of 167 proteins were identified. Among them, 37 were found unique for T. equiperdum. One of them, the variant surface glycoprotein (SCU70408.1), could represent a good candidate for the development of a serological diagnostic test specific for T. equiperdum.